2016
DOI: 10.1002/brb3.591
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isoflurane anesthesia on resting‐state fMRI signals and functional connectivity within primary somatosensory cortex of monkeys

Abstract: IntroductionCorrelated low‐frequency fluctuations of resting‐state functional magnetic resonance imaging (rsfMRI) signals have been widely used for inferring intrinsic brain functional connectivity (FC). In animal studies, accurate estimate of anesthetic effects on rsfMRI signals is demanded for reliable interpretations of FC changes. We have previously shown that inter‐regional FC can reliably delineate local millimeter‐scale circuits within digit representations of primary somatosensory cortex (S1) subregion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 53 publications
3
50
0
Order By: Relevance
“…For example, it has been shown that with increased anesthesia levels, functional connectivity decreases between cortices in macaque monkeys [17]. Similarly, we have also reported diminishing contributions of low frequency fluctuations and correlation strengths between regions in the primary somatosensory cortex of squirrel monkeys as anesthesia levels were increased [18]. A recent observational study in rhesus monkeys on dose-dependent effects of anesthesia on regional activity also demonstrated a similar phenomenon [19].…”
Section: Introductionsupporting
confidence: 72%
“…For example, it has been shown that with increased anesthesia levels, functional connectivity decreases between cortices in macaque monkeys [17]. Similarly, we have also reported diminishing contributions of low frequency fluctuations and correlation strengths between regions in the primary somatosensory cortex of squirrel monkeys as anesthesia levels were increased [18]. A recent observational study in rhesus monkeys on dose-dependent effects of anesthesia on regional activity also demonstrated a similar phenomenon [19].…”
Section: Introductionsupporting
confidence: 72%
“…However, unlike prior studies, which largely relied on variations of depth of anesthesia, our comparison of awake states and anesthesia also suggested that the visual networks and their connectivity with default and frontoparietal networks actually showed anesthesia-related increases in connectivity. Overall, these findings echo recent studies of the impact of anesthetics on brain differences in humans, which suggested a loss of complexity in the functional architecture of the brain (Chang et al, 2016; Hutchison et al., 2014; Peltier et al, 2005; Smith et al, 2017; Wu et al, 2016). Further work will be required to rule out other possibilities, such as differences in respiration associated with differing states (awake or anesthesia).…”
Section: Discussionsupporting
confidence: 86%
“…Unlike traditionally defined neocortical areas, which are grounded in architectonics, they are not necessarily expected to be stable across all conditions, as FC patterns are known to vary as a function of state. Previous studies have demonstrated that FC patterns are sculpted more by structural connectivity under deep anesthesia than the awake state (Barttfeld and Uhrig, 2015; Wu et al, 2016). In anesthesia states, when isoflurane levels were varied, the signal fluctuations and connectivity also exhibited distinct profiles at each level within the same animal (Smith et al, 2017; Gao et al, 2017; Peltier et al, 2005; Hutchison et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although the methods of identification and the nomenclature for naming them have been different, similar anatomical patterns have been detected through temporal correlations. The correlated areas suggest that many elements of the resting state may be conserved across primate species and even other mammals [Damoiseaux et al, 2006;Vincent et al, 2007;Kannurpatti et al, 2008;Pawela et al, 2008;Hutchison et al, 2011;Hutchinson and Everling, 2012;Barks et al, 2015;Wu et al, 2016]. Interestingly, recent works have argued that resting-state activity may underlie rudimentary brain functioning, showing that several brain regions can be tonically active at rest, maximizing the efficiency of information transfer while preserving a low physical connection cost [Bullmore and Sporns, 2009;Hutchinson and Everling, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…Low-frequency fluctuations (less than 0.1 Hz) in the blood oxygen leveldependent (BOLD) signals are detected [Fox and Greicius, 2010] and can be observed regardless of the type of anesthetic used [Horwitz, 2003;Vincent et al, 2007;Kannurpatti et al, 2008;Zhao et al, 2008;Hutchison et al, 2010;Wu et al, 2016]. Functional connectivity is defined as the temporal correlations between brain structures [Beckmann et al, 2005;Bonnefond et al, 2017].…”
Section: Introductionmentioning
confidence: 99%